2018
DOI: 10.1680/jgein.17.00032
|View full text |Cite
|
Sign up to set email alerts
|

Geosynthetic reinforcement of pile-supported embankments

Abstract: Rigid piles are used to reinforce soft soil base and increase embankment stability. This technique is improved by placing one or more geosynthetic reinforcement (GR) layers inside or at the base of the embankment. A series of 33 small scale models has been tested using a geotechnical centrifuge. Soft soil settlement is imposed by the downward displacement of a tray. First, a series of models is prepared to examine how the load transmitted to the pile network increases with the embankment thickness. For a same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 29 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…A few such analyses were presented in the literature [ 5 , 6 , 7 , 8 , 9 ], but they are very time-consuming. However, numerical analyses are often reduced to two dimensions by assuming plane strain conditions or axial symmetry when the behavior of one column is analyzed, e.g., [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Wijerathna and Liyanapathirana [ 18 ] compared numerical predictions from 2D-EA (two-dimensional model based on the equivalent area approach) and the 3D models and proposed a method to quantify the parameters for the EMC (an extension of the Mohr-Coulomb model) model simulating the column behavior when converting a 3D field embankment into a 2D-EA model or vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…A few such analyses were presented in the literature [ 5 , 6 , 7 , 8 , 9 ], but they are very time-consuming. However, numerical analyses are often reduced to two dimensions by assuming plane strain conditions or axial symmetry when the behavior of one column is analyzed, e.g., [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Wijerathna and Liyanapathirana [ 18 ] compared numerical predictions from 2D-EA (two-dimensional model based on the equivalent area approach) and the 3D models and proposed a method to quantify the parameters for the EMC (an extension of the Mohr-Coulomb model) model simulating the column behavior when converting a 3D field embankment into a 2D-EA model or vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies on the influence of the end bearing condition and modulus of piles on the performance of GRPSEs of Shen et al [ 19 ] suggested that piles with relatively low modulus could increase the total settlement of bottom piles and foundation soil, and ultimately promote the lateral displacement of the embankment slope. In addition, many recent studies have extensively studies the critical factors that govern the load transfer mechanism and surface settlement of a GRPSE system, such as pile spacing, embankment height, pile cap size, GR stiffness and number of layers of geogrid [ 5 , 20 23 ]. Furthermore, Wang and Mei [ 24 ] found that the micro-piles can improve the stability and deformation characteristics of the soft soil foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent composite foundation is widely used for the construction of embankments on soft ground [26,27]. Geosynthetics (such as geotextiles and geogrids) with high tensile strength, low elongation, and high stiffness are laid at the bottom of embankment which form reinforced cushion with gravel to maintain the integrity and continuity of the base [28][29][30]. Reinforced cushion and concrete pile constitute composite foundation of reinforced pile group.…”
Section: Introductionmentioning
confidence: 99%